A modified biopsy needle with pole for repeatable tissue extraction from free‐ranging crocodiles - Daniel Barrow; Andrew R. Halford (Wildlife Society Bulletin)
ABSTRACT Biopsy sampling is a powerful tool for furthering our understanding of animal populations. Knowledge of diets and trophic energy flows, genetic structure and connectivity between populations, and uptake of environmental contaminants can all be elucidated through analysis of animal tissues, which is particularly useful for animals that are elusive and difficult to observe. Crocodylians are an aquatic group for which biopsy sampling is an appropriate tool; however, sample collection usually requires undertaking the arduous and dangerous process of capturing individual crocodiles. We describe a biopsy system that employs a modified version of a standard biopsy needle and pole kit to consistently extract crocodile tissue with greatly reduced effort and increased safety. This system takes advantage of the behavioral trait of crocodiles to “freeze” under the glare of a high‐powered spotlight, enabling an approach to within a few meters. We field‐tested the system in 2 remote river systems in northwestern Australia, during July–August 2015, collecting tissue samples from 69 crocodiles (Crocodylus porosus; size range = 0.9–4.4 m total length) with approximately 95% success. The pole biopsy system increases sample collection efficiency by removing the need to handle individual crocodiles. Moreover, this decreases stress on the crocodile population and significantly reduces the number of field crew required. © 2019 The Wildlife Society.